2020
DOI: 10.2196/15682
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Video Visits Using Veterans Affairs Telehealth Tablets: Survey Study

Abstract: Background Video-based health care can help address access gaps for patients and is rapidly being offered by health care organizations. However, patients who lack access to technology may be left behind in these initiatives. In 2016, the US Department of Veterans Affairs (VA) began distributing video-enabled tablets to provide video visits to veterans with health care access barriers. Objective This study aimed to evaluate veterans’ experiences with VA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 41 publications
7
103
1
Order By: Relevance
“…Indeed, a recent study estimated that 38% of Medicare beneficiaries were unready to engage in home telehealth 19 . However, when given the opportunity, many older patients can effectively engage in telehealth 13,20‐25 . We hypothesized that telehealth might improve access to care, but we were unsure if our patients were interested or if they had the technology and confidence to attempt a home telehealth visit 1 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study estimated that 38% of Medicare beneficiaries were unready to engage in home telehealth 19 . However, when given the opportunity, many older patients can effectively engage in telehealth 13,20‐25 . We hypothesized that telehealth might improve access to care, but we were unsure if our patients were interested or if they had the technology and confidence to attempt a home telehealth visit 1 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Patients feel that telemedicine yields high satisfaction, allows good communication, saves time, and is cost-effective. [5][6][7][8][9][10] Telemedicine decreases hospitalization rates and visits to the emergency room. 6 Studies also found that telemedicine yields similar results as face-to-face encounters.…”
Section: Introductionmentioning
confidence: 99%
“…6 Studies also found that telemedicine yields similar results as face-to-face encounters. 8,9,[11][12][13][14] It was even considered to be the major channel for care delivery 15 ; however, its implementation and usage have still been relatively low. 16 The advent of the COVID-19 outbreak resulted in a rapid and significant adoption of telemedicine for both chronic and acute conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Authors * Elaine C Khoong, MD MS 1,2 * Blythe A Butler, BA 3 Omar Mesina, MD 3,4 George Su, MD 5 Triveni B DeFries, MD MPH 1 Malini Nijagal, MD MPH 6 Courtney R Lyles, PhD Before the COVID-19 pandemic, telemedicine video visits were uncommon, especially within safety-net settings. A 2018 survey found only 44% of community health centers used any telehealth.…”
mentioning
confidence: 99%
“…[3] Prior studies on interest in video visits focused on the subset of patients who had already completed a video visit, representing early adopters who are likely different from the general population. [4,5] As telemedicine becomes a standard modality for healthcare, little is known about the interest in or challenges to video visits among low-income, diverse racial/ethnic, or non-English speaking populations. These populations already face disparities accessing healthcare and are already less likely to use digital health tools due to disparities in device ownership, broadband access, and digital literacy.…”
mentioning
confidence: 99%